2012
DOI: 10.1007/s11695-012-0684-2
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Greater Curvature Plication (LGCP) for Treatment of Morbid Obesity in a Series of 244 Patients

Abstract: Over the short term, LGCP results in effective weight loss and significant T2DM reduction with a very low rate of complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 24 publications
3
28
1
2
Order By: Relevance
“…The current evidence on laparoscopic gastric plication for severe obesity raises no major safety concerns in short-to-medium term but more evidence is needed about the long-term efficacy of the procedure (EL B [129][130][131][132][133][134] ).…”
Section: Adjustable Gastric Banding (Agb) -Sleeve Gastrectomy (Sg) mentioning
confidence: 99%
“…The current evidence on laparoscopic gastric plication for severe obesity raises no major safety concerns in short-to-medium term but more evidence is needed about the long-term efficacy of the procedure (EL B [129][130][131][132][133][134] ).…”
Section: Adjustable Gastric Banding (Agb) -Sleeve Gastrectomy (Sg) mentioning
confidence: 99%
“…Recent procedures in which long-term outcome data is not yet available include: Laparoscopic gastric plication (LGP) in which infolding of the greater curvature of the stomach leads to tubularizing the stomach through intraluminal tissue fold. The current evidence on laparoscopic gastric plication for severe obesity raises no major safety concerns in short-to-medium term but more evidence is needed about the long-term efficacy of the procedure (EL B [129][130][131][132][133][134] ).…”
Section: Surgical Techniques Overviewmentioning
confidence: 99%
“…7 Fried et al found that there were no differences between single-row plications and two-row plications in terms of weight loss and complication rates. 5 It is recommended that the plication is better to be done in at least two rows. Two-row plication is not only more effective and durable but also helps to make a better plication with uniform tension and to avoid the herniation of gastric wall between stitches.…”
Section: Resultsmentioning
confidence: 99%